(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2024)
Background. Sulfoximines recently gained significant attention of researchers as bioisosteric analogs of sulfone, amide, sulfonamide, and other related structural fragments. On the other hand, incorporation of fluorine atoms is a well-known tool in medicinal chemistry allowing to improve pharmacokinetic and physicochemical parameters of biologically active compounds. Therefore, development of effective approaches towards fluorine-containing sulfoximines, in particular, with additional functional groups, as well as establishing effects of their structure on the main physicochemical properties, is an important task. The goal of this work is to develop scalable protocols for the synthesis of 1-bromo-4-(S-(fluoroalkyl)sulfonimidoyl)benzenes and to establish effect of the fluorine atoms and the sulfoximine fragment on lipophilicity (as compared to the non-fluorinated analogs and the corresponding sulfones). Objects. Aromatic sulfoximines and sulfones with fluorinated alkyl side chains. Methods. Scalable organic synthesis of aromatic sulfoximines with fluorinated alkyl side chains; structure investigation and characterization of the synthesized compounds by 1H, 19F, 13C NMR spectroscopy and chromatomass-spectrometry; lipophilicity measurement by liquid-liquid extraction in combination with HPLC. Results. Based on the known approach to the sulfoximine synthesis that includes introduction of the imine fragment by oxidation of the corresponding aryl fluoroalkyl sulfide with phenyliodosodiacetate in the presence of ammonium carbamate, scalable protocols for the synthesis of 1-bromo-4-(S-(fluoroalkyl)sulfonimidoyl)benzenes were developed (fluoroalkyl – CH2F, CHF2, CF3). Using liquid-liquid extraction in combination with HPLC (“shake-flask” protocol), lipophilicity of the obtained compounds (i.e., 1-octanol – water distribution coefficient logarithm, LogP) was determined and compared with the values for the non-fluorinated analogs and the corresponding sulfones. Conclusions. It is shown that the approach to the synthesis of sulfoximines that includes oxidation of the corresponding alkyl aryl sulfide with phenyliodosodiacetate in the presence of ammonium carbamate, is efficient to obtain fluorinated derivatives in multigram quantities. It is found that fluorination of 1-bromo-4-(S-methylsulfonimidoyl)benzene at the methyl group leads to the stepwise increase the molecule’s lipophilicity (by ca. 0.6 LogP units per each fluorine atom on average), while replacement of the sulfone moiety with sulfoximine in the studied series lowers it by ca. 0.7 LogP units.